La educación en las ideas políticas de Alberdi y Sarmiento - Curto, Jorge Christian (2013)
Alberdi and Sarmiento had different ideas regarding the concept of education. I consider that those ideas are important to understand their political plans. Alberdi considered that Argentina had to receive immigration to develop as a nation and that the education of its people did not have to be a priority. Sarmiento rejects Alberdi's ideas. Sarmiento considered that Argentine had to receive immigration, but he also believed that one of the Argentine's priorities was to eradicate illiteracy. The purpose of this essay is to analyze the ideas of those two intellectuals regarding education and to reflect about the elements that should be present to create a prosperous nation.